M-Learning in the development of speaking skills - Puco Chicaiza, Cristian Rodrigo (2021)
This research with the name “M-Learning in the Development of English Speaking Skills in First Baccalaureate Students at Marco Aurelio Subía Martínez - Batalla De Panupali Educative Unit”. Has as the main objective to analyze Mobile learning in the development of speaking. The research was descriptive, qualitative, and not experimental. It was descriptive because it was described both variables (M-learning and speaking skills) in the theoretical framework, moreover, M-learning influences speaking skills. Besides, the research carried out a qualitative approach to analyze and describe the results obtained by the survey; the technique applied in this study, whose instrument was a questionnaire thus, it was identified the lack of use of mobile devices with educational purposes in English classes. To validate the proposal, which was a booklet entitled “M-learning to develop speaking skills”. It was applied a checklist as a technique and a questionnaire as an instrument to three experts and two users; the results affirmed that mobile applications could positively influence the development of speaking skills. Finally, the researcher socialized the proposal with his English colleagues. To conclude the four interactive applications used in the proposal and based on practicing, interacting, learning vocabulary and grammatical structures were very attractive and interesting for teachers, thus, being useful curricular tools in the teaching and learning of the English language in the classrooms.